Professores e políticas de centralização curricular: uma análise do processo na construção do currículo da cidade de São Paulo na perspectiva habermasiana - Alves, Natalia Torres Colombo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
A Secretaria Municipal de Educação de São Paulo (SME) empreendeu um caminho próprio de construção curricular, no qual as propostas da BNCC foram articuladas com outros estudos tomados pela equipe como adequados à orientação para a sua implementação. A referida construção curricular da SME colocou-se como um projeto colaborativo, coletivo e autoral, organizado a partir de grupos de trabalho representativos da rede, envolvendo professores, especialistas em educação, familiares/responsáveis pelos estudantes, estudantes; em debates e na elaboração de propostas. Destarte, a presente pesquisa objetivou investigar — a partir do discurso oficial expresso por documentos e por pessoas que participaram como gestores, formadores e professores do Grupo de Trabalho de Matemática — as práticas de construção do Currículo da Cidade de São Paulo, enfatizando o papel das professoras e professores de Matemática nesse processo, identificando as bases teóricas que subsidiam os conceitos de “currículo” e “participação de professores”, descrevendo os mecanismos/processos utilizados para construção curricular, caracterizando os espaços de interação, bem como as ações promovidas pela Secretaria Municipal de Educação para o envolvimento de professores. Para tanto, metodologicamente, o estudo conta com análise de documentos e de conversas com pessoas que participaram no processo de construção do Currículo da Cidade. A análise empreendida dos documentos evidencia declaração oficial de que os mecanismos e processos da construção e implementação do currículo foi pautada nos ideais de William Doll, concebendo currículo a partir de uma natureza não linear, e construída na interação entre partícipes. A partir das conversas realizadas, em reunião coletiva online pautada nos princípios do Agir Comunicativo de Jürgen Habermas, rememorações e buscas por entendimentos do processo possibilitaram analisar fragmentos de narrativas de experiências que evidenciaram características de democracia deliberativa na tentativa de superar as limitações impostas por políticas de centralização curricular.

The Municipal Education Department of São Paulo (SME) undertook its own path of curriculum construction, in which the BNCC proposals were articulated with other studies considered by the team as adequate to guide its implementation. The aforementioned curricular construction of the SME was placed as a collaborative, collective and authorial project, organized from working groups representing the network, involving teachers, education specialists, family members/guardians of students, students; in debates and in the elaboration of proposals. Thus, the present research aimed to investigate — from the official discourse expressed by documents and by people who participated as managers, trainers and teachers of the Mathematics Working Group — the practices of construction of the Curriculum of the City of São Paulo, emphasizing the role of teachers and Mathematics teachers in this process, identifying the theoretical bases that support the concepts of "curriculum" and "teacher participation", describing the mechanisms/processes used for curriculum construction, characterizing the spaces of interaction, as well as the actions promoted by the Department Municipal Education for the involvement of teachers. Therefore, methodologically, the study relies on document analysis and conversations with people who participated as managers, teacher trainers, and Mathematics teachers who worked in the process of building the City Curriculum. From these, results have already been obtained, in which the analysis carried out of the theoretical bases present in the official documents issued by the Municipal Department of Education, in the didactic guidelines and in the curricular prioritizations, namely the documents: Curriculum Guidelines and Proposition of Learning Expectations, Curriculum Integrator da Infância Paulistana, Learning Rights of Interdisciplinary and Author Cycles and in these documents it is possible to identify the official statement that the mechanisms and processes of the construction and implementation of the curriculum were guided by the ideals of William Doll, conceiving curriculum from a non- linear, and built on the interaction of the participants. In the analysis of the dialogues with the participants of the curriculum construction process, obtained from an online group meeting, Jürgen Habermas' principles of Communicative Action were used, seeking to recover memories, build understandings and express feelings about the referred process. In the end, the intention was to analyze fragments of narratives of experiences of the participants of the Mathematics WGs - in the stages of construction and implementation of the curriculum - observing in the episodes the search for intelligibility, sincerity and the intention of the formation of a public sphere focused on the curriculum. In this way, in the analysis, evidence of a process with characteristics of deliberative democracy is observed, it is argued that with the possession of this reference and under the methodological guidelines described, it is possible to have a humanized and democratic curriculum, taking advantage of the participation of those involved in the process and overcoming the limitations imposed by curricular centralization policies.
Teachers and curriculum centralization policies: an analysis of the process in the construction of the curriculum of the city of São Paulo in the Habermasian perspective
Keywords: Grupos de Trabalho de Matemática (GT); Currículo da Cidade de São Paulo; Construção e implementação do currículo; Mathematics Working Groups (GT); Curriculum of the City of São Paulo; Construction and implementation of the curriculum